(untitled) (Pakistan Journal of Science, 2015)
A descriptive epidemiological study was carried out for understanding the ranking order and temporal distribution of parturient haemoglobinuria in buffalo. For this data was recorded from each household of eight randomly selected villages. Parturient haemoglobinuria ranked as number one disease among all observed cases with respect to mortality (1.03%) and proportional mortality (29.41%) rate and appeared as 4thand 3rdposition in ranking with respect to incidence (3.97%) and case fatality (25.97%) rate. For assessment of temporal distribution, data of 77 haemoglobinuria cases was analyzed. Significantly (P<0.05) increased proportion of haemoglobinuria cases were recorded during December (23.3%) and in 4th lactation (31.1%). Majority (62.22%) of pregnant animals were affected during or after 7th month of pregnancy whereas; significantly (P<0.05) increased proportion (68.88%) of non pregnant animals was affected within 60 days of parturition. Findings indicated that parturient haemoglobinuria was among most important diseases of breeding age buffaloes causing 29.41% of the total deaths.